Anterior Circulation Fusiform Aneurysms Have a Lower Occlusion Rate After Pipeline Embolization Device Treatment Than Posterior Circulation Fusiform Aneurysms: A Multicenter Cohort Study - Xu, Chao; Wu, Pei; Zou, Liang; Xu, Shancai; Luo, Bin; Yang, Xinjian; Shi, Huaizhang (Frontiers in Neurology, 2022)
Abstract Objective: Intracranial fusiform aneurysms are uncommon and can occur in vessels of the anterior circulation (AC) or posterior circulation (PC). While flow diversion is one treatment option, research into Pipeline Embolization Device (PED) treatment is lacking. This study explored the efficacy and safety of PED treatment for intracranial fusiform aneurysms, and compared therapeutic effects between AC and PC aneurysms. Methods: In the post-market multi-center cohort study of embolization of intracranial aneurysms with PED in China (PLUS) registry study, we retrospectively analyzed 71 fusiform aneurysms in 67 patients among 1,171 patients treated with a PED from November 2014 to October 2019. The general characteristics, perioperative status, aneurysm occlusion rate at the last follow-up angiography, and changes in modified Rankin Scale scores were analyzed. Aneurysms were divided into AC and PC groups, and univariate and multivariate analyses were conducted. Results: The study included 26 AC (25 patients) and 45 PC (42 patients) aneurysms. A total of 75 PEDs were used, an average of 1.1 PEDs were used, and the median follow-up was 6.7 months. Fifty aneurysms (71.4%) were occluded and twenty (28.5%) were incompletely occluded. There were significantly more occluded aneurysms in the PC group than in the AC group (12 vs. 38; P = 0.001). Risk factors for incomplete occlusion were AC aneurysms (P = 0.001) and a perforating artery originating from the aneurysm (P = 0.006). The mean modified Rankin Scale score was significantly lower at the last follow up than preoperatively (0.58 vs. 0.21; P = 0.0001). Conclusion: Non-overlapping PED is a safe and effective treatment for both AC and PC fusiform aneurysms. The occlusion rate of AC fusiform aneurysms is lower than that of PC.